2022
DOI: 10.24843/eja.2022.v32.i04.p11
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan di Bursa Efek Indonesia

Abstract: Disclosure of social responsibility is a form of delivery from the company to stakeholders for the commitment made by the company to maintain and maintain the components affected by the operational activity process based on the Triple Bottom Line concept. The research has the aim of knowing the effect of profitability and company size on the disclosure of social responsibility. The proxy used in this study is the level of profitability which is proxied through the ROA ratio and company size which is calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 4 publications
1
4
0
7
Order By: Relevance
“…ROA net income is better able to predict future investment returns (Kusuma, 2021). The calculation of profitability using ROA measures the company's effectiveness in generating profits by utilizing its assets (Puspitasari et al, 2019). Assessing a company's ability to generate value from its assets can be done by examining ROA.…”
Section: Measurement Of Variablesmentioning
confidence: 99%
“…ROA net income is better able to predict future investment returns (Kusuma, 2021). The calculation of profitability using ROA measures the company's effectiveness in generating profits by utilizing its assets (Puspitasari et al, 2019). Assessing a company's ability to generate value from its assets can be done by examining ROA.…”
Section: Measurement Of Variablesmentioning
confidence: 99%
“…A high number of executive commissioners should prove and encourage management to issue sustainability reports in an effort to meet stakeholder needs. Research by Putri & Pramudiati (2019) and Madona & Khafid (2020) concluded that the board of independent commissioners has no influence on the imperishable report. On the other hand, Putri & Pramudiati's research (2019) and Madona & Khafid (2020) are contradictory to Liana (2019).…”
Section: Picture 1 Disclosure Intensity Of Imperishable Reportmentioning
confidence: 99%
“…Menurut teori kontrak sosial, perusahaan yang mendapatkan peringkat PROPER yang bagus, penghargaan ini cukup menjadi bukti bagi masyarakat umum tentang bagaimana seharusnya perusahaan melakukan kegiatan lingkungan dan sosial. Oleh karena itu, manajemen berpendapat bahwa perusahaan tidak perlu mengungkapkan informasi CSR secara terperinci dalam laporan tahunan (Puspitasari et al, 2019). Hasil penelitian ini mendukung penelitian Sirait & Bangun (2013) dan Puspitasari et al (2019) yang mana variabel kinerja lingkungan berpengaruh negatif terhadap pengungkapan Corporate Social Responsibility.…”
Section: Pengaruh Kinerja Lingkungan Terhadap Pengungkapan Corporate ...unclassified
“…Oleh karena itu, manajemen berpendapat bahwa perusahaan tidak perlu mengungkapkan informasi CSR secara terperinci dalam laporan tahunan (Puspitasari et al, 2019). Hasil penelitian ini mendukung penelitian Sirait & Bangun (2013) dan Puspitasari et al (2019) yang mana variabel kinerja lingkungan berpengaruh negatif terhadap pengungkapan Corporate Social Responsibility. Sedangkan, hasil penelitian ini tidak mendukung penelitian yang dilakukan oleh Badilah et al (2021) dan Ramadhan (2019) yang menujukkan bahwa variabel kinerja lingkungan berpengaruh positif dan signifikan terhadap pengungkapan corporate social responsibility.…”
Section: Pengaruh Kinerja Lingkungan Terhadap Pengungkapan Corporate ...unclassified
See 1 more Smart Citation